Inactivation of the Lipid-Containing Bacteriophage PM2 by Butylated Hydroxytoluene - Cupp, James (1975)
Several factors have been investigated which are of significance in the inactivation of PM2, a lipid-containing bacterial virus, by butylated hydroxytoluene (BHT). Studies of the time dependence of inactivation during exposure to BHT showed that virus killing occurs rapidly, with the majority of the effect taking place in the first 5 min. The degree of inactivation is dependent upon the initial virus titer, the solvent from which BHT is added, and the presence of a variety of protective agents, including surfactants, bovine serum albumin, and bacterial cells. Sucrose gradient analysis of (32)P-labeled, BHT-treated virus was used to determine the degree to which the virion is disrupted by BHT. These experiments show that the (32)P-labeled molecules are converted into very slowly sedimentable material by BHT treatment, indicating complete destruction of the virus particle.